Un análisis bibliométrico del brand equity 1991-2018; A bibliometric analysis of brand equity 1991-2018 - Samir Ricardo Neme-Chaves; Liliana Yamile Rodríguez-González (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– This document provides a bibliometric analysis of the current state of the brand equity research by mapping the research landscape to identify more productive authors and countries over time, analysis of publications, cooperation between authors, co-appointments, co-occurrences of keywords; plus, identification of research clusters to visualize the conceptual structure of the field of knowledge. Using the Scopus collection, this study analyzes 2000 publications that study brand equity. Identify four major research groups: brand equity, empirical analysis, the services sector and the common methodology of the studies, which characterize the different research trends and analyze the most preponderant fields of action for the understanding of brand equity; new studies are proposed that include a traditional systematic review to complement what is stated in this document. This research provides an overview that can be a valuable guide for teachers, researchers and professionals.
Keywords: M00; M30; M31; M39; 330; bibliometrics; brand equity; scientific productivity; scientific cooperation